Evaluation of early left-sided cardiac reverse remodeling under combined therapy of sacubitril-valsartan and spironolactone compared with angiotensin-converting enzyme inhibitors and spironolactone - Sacharczuk, Wioletta; Dankowski, Rafał; Ożegowski, Stefan; Rojna, Maciej; Szyszka, Andrzej (Frontiers in Cardiovascular Medicine, 2023)
We aimed to compare therapies of sacubitril/valsartan+spironolactone (S/V+S) with angiotensin-converting enzyme inhibitors+spironolactone (ACEI+S) on the left-sided cardiac reverse remodeling (L-CRR). The second objective was to analyze the usefulness of GLS and LVEF in response to therapy. Methods. 78 patients (mean age 63.4 years, 20 females) with symptomatic heart failure with reduced ejection fraction were randomized to groups of equal numbers, i.e. 39 patients, and started on therapy of S/V+S or ACEI+S. Second evaluations were made after 6-8 weeks of therapy. Results. GLS changed from -7.4% to -9.4 % (18% improvement) in both arms equally. More than 50% of patients, initially with very severe systolic dysfunction (GLS>-8%), were reclassified to severe (GLS -8%- -12%). LVEF did not improve in any of the groups. The quality of life measured by MLHFQ and walking distance by 6-MWT increased. Positive correlations between GLS and 6MWT (r = 0.41, p = 0.02) and GLS and MHFLQ (r = 0.42, p = 0.03) were found. The S/V+S subgroup demonstrated improvements in LVEDV (∆16.7 vs 4.5ml), E/e ratio (∆ 2.8 vs 1.4), and LAVI (∆ 9.4 vs 8.4 ml/m2) as compared to ACEI+S. Conclusion. GLS, unlike LVEF, detects early changes in LV systolic function after 6-8 weeks of combined therapy, i.e. SV+S and ACE+S. GLS is more useful than LVEF in assessing early response to treatment. The effect of S/V+S and ACEI+S on LV systolic function was comparable, but the improvement in diastolic function as expressed by E/e', LAVI, and LVEDV was more pronounced with S/V+S.